1996
DOI: 10.1002/pen.10694
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and pyroelectric characterization of anionic and native collagen

Abstract: Reconstituted collagen membranes (thickness 20–40 microns), used in periodontal guided tissue regeneration, were prepared by solubilization of bovine serosa and bovine tendon using an alkaline treatment and by solubilization of bovine serosa in acetic acid. Dielectric properties of these materials were determined in the frequency range of 10−5−106 Hz (poling temperature = 313 K, poling time = 3 h, E = 107 V/m), using a General Radio Bridge system (high frequencies) and a discharge current technique (low freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(60 citation statements)
references
References 19 publications
7
51
0
2
Order By: Relevance
“…Different band absorptions were possibly attributed to the different molecular structures between both collagens. The ratio of absorption intensities between 1240 cm −1 (amide III) and 1448 cm −1 band was approximately equal to 1.0, confirming the triple helix structure of the collagen extracted from the Nile Tilapia and is in accordance with Guzzi Plepis et al [36]. The position of the band was found to be shifted to lower frequency (1546 cm −1 ) as compared to the normal absorption range of amide II band (1550-1600 cm 1 ), which suggests the existence of hydrogen bonding in each collagen.…”
Section: Discussionsupporting
confidence: 88%
“…Different band absorptions were possibly attributed to the different molecular structures between both collagens. The ratio of absorption intensities between 1240 cm −1 (amide III) and 1448 cm −1 band was approximately equal to 1.0, confirming the triple helix structure of the collagen extracted from the Nile Tilapia and is in accordance with Guzzi Plepis et al [36]. The position of the band was found to be shifted to lower frequency (1546 cm −1 ) as compared to the normal absorption range of amide II band (1550-1600 cm 1 ), which suggests the existence of hydrogen bonding in each collagen.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, bands of amide III are also present at 1338 cm −1 /1336 cm −1 , correspondent to the NH bending associated with CN stretching, and at 1240 cm −1 /1244 cm −1 , relative to C-O stretching, respectively. The absorption ratio between the amide III and 1450 cm −1 peaks was near to 1 (1.01 for salmon and 0.97 for codfish), which was an indicator of the preservation of the triple helix structure of collagen [49,[53][54][55][56]. These findings are similar to other findings found in the literature for other marine species [42,[57][58][59], as well as the ones in this study [41].…”
Section: Ftir Analysissupporting
confidence: 91%
“…For typical ASC, five peaks could be observed in its FTIR spectrum: the amide A band is associated with the N-H stretching frequency; the amide B band represents the asymmetrical stretch of CH 2 ; the amide I band is originated from C=O stretching vibrations coupled to N-H bending vibrations, CN stretch and CCN deformation; the amide II indicates that the N-H is involved in bonding with the adjacent α-chains; the amide III represents the combination peaks between C-N stretching vibrations and N-H deformation from amide linkages as well as absorptions arising from wagging vibrations from CH 2 groups of the glycine backbone and proline side-chains; in addition, the triple helical structure of ASC was confirmed from the absorption ratios between amide III and 1456 cm -1 band, which was approximately equal to 1.0 (Guzzi Plepis et al, 1996). For ASC-S, ASC-D, and ASC-R, all the typical characters of ASC were observed, and the FTIR spectra clearly showed the helical arrangements of them.…”
Section: Ultrastructurementioning
confidence: 97%
“…For fraction D2 with AMW of 1.29 kDa, its MW distribution completely focused on the retention time of 23 to 24 min (data not show here), and its infrared spectrum was completely different from those of ASC-D and D1. The bands of amide III and 1456 cm -1 disappeared, which indicated that the triple helical structure of D2 was completely destroyed (Guzzi Plepis et al, 1996).…”
Section: Ftir Studymentioning
confidence: 99%